Causal relationship between genetic-predicted uric acid and cervical cancer risk: evidence for nutritional intervention on cervical cancer prevention - Cao, Chunge; Cai, Dajun; Liu, Hao; Zhang, Xia; Cai, Lina; Sun, Caiping; Wang, Huifang; Zhao, Hu; Yue, Chaoyan (Frontiers in Nutrition, 2024)
This study aimed to investigate the causal relationship between serum uric acid (SUA) levels and cervical cancer incidence, and to evaluate the potential role of nutritional interventions in cervical cancer prevention. We conducted a two-sample bidirectional Mendelian randomization (MR) analysis using genetic instruments from publicly available genome-wide association studies (GWASs) of individuals of predominantly European ancestry. Methods such as inverse-variance weighted, weighted-median, weighted model, and MR-Egger were applied. Sensitivity tests, including leave-one-out, MR-PRESSO, and Cochran's Q test, assessed heterogeneity and pleiotropy. Our findings revealed that a high SUA concentration significantly increased the risk of malignant cervical cancer: a 1 mg/ml increase in SUA was associated with a 71% higher risk (OR = 1.71, 95% CI=1.10-2.67; P=0.018). Stratification by histological type showed a significant causal effect on cervical adenocarcinoma risk (OR = 2.56, 95% CI=1.14-5.73; P=0.023). However, no clear evidence was found for a causal effect of cervical cancer on SUA levels. In conclusion, this study identified a causal relationship between elevated SUA levels and the risk of malignant cervical cancer, particularly cervical adenocarcinoma. These findings provide novel insights into the mechanisms of cervical carcinogenesis and suggest that managing SUA levels could be a potential strategy for cervical cancer prevention through dietary management.